The legal status of transsexual and transgender persons / edited by Jens M. Scherpe. - Scherpe, Jens M., 1971- (Intersentia Ltd., 2015)
The need to allow a change of legal sex/gender in certain cases is no longer disputed in most jurisdictions, and for European countries there is no question as to whether such a change should be allowed after the decision of the European Court of Human Rights in Goodwin v. United Kingdom (Application no. 28957/95). The question has therefore shifted to what the requirements for such a change of the legal sex/gender should be. Many jurisdictions have legislated or developed an administrative approach to changing sex/gender, but the requirements differ significantly from jurisdiction to jurisdiction, particularly with regard to age, nationality and marital status, as well as the medical and psychological requirements. The latter in some jurisdictions still include surgery and sterility as a precondition, thus potentially forcing the persons concerned to choose between the recognition of their sex/gender identity and their physical integrity. The book also examines questions that are thus far under-researched, namely what the full legal consequences of a change of legal sex/gender should be, for example with regard to existing legal relationships such as marriages and registered partnerships, but also concerning children and parentage. The Legal Status of Transsexual and Transgender Persons is the result of an international research project, including not only national reports from 14 European and non-European jurisdictions but also two chapters that look at legal sex/gender changes from a Christian perspective and one chapter from a medical-psychological perspective. The final comparative chapter compares and contrasts the different approaches and requirements and makes recommendations for best practice and law reform.